Whitewalling art, race & protest in 3 acts - D'Souza, Aruna 1969- (Badlands Unlimited, 2018)
In 2017, the Whitney Biennial included a painting by a white artist, Dana Schutz, of the lynched body of a young black child, Emmett Till. In 1979, anger brewed over a show at New York's Artists Space entitled Nigger Drawings. In 1969, the Metropolitan Museum of Art's exhibition Harlem on My Mind did not include a single work by a black artist. In all three cases, black artists and writers and their allies organized vigorous responses using the only forum available to them: public protest. 'Whitewalling: Art, Race, & Protest in 3 Acts' reflects on these three incidents in the long and troubled history of art and race in America. It lays bare how the art world - no less than the country at large - has persistently struggled with the politics of race, and the ways this struggle has influenced how museums, curators and artists wrestle with notions of free speech and the specter of censorship. 'Whitewalling' takes a critical and intimate look at these three "acts" in the history of the American art scene and asks: when we speak of artistic freedom and the freedom of speech, who, exactly, is free to speak?
Keywords: Geschichte 1969-2017; Rassismus; Kunst; USA; Art and race / History; Freedom and art / United States / 20th century; Nonfiction